2022
DOI: 10.1002/jgt.22868
|View full text |Cite
|
Sign up to set email alerts
|

Making an H $H$‐free graph k $k$‐colorable

Abstract: We study the following question: How few edges can we delete from any H $H$‐free graph on n $n$ vertices to make the resulting graph k $k$‐colorable? It turns out that various classical problems in extremal graph theory are special cases of this question. For H $H$ any fixed odd cycle, we determine the answer up to a constant factor when n $n$ is sufficiently large. We also prove an upper bound when H $H$ is a fixed clique that we conjecture is tight up to a constant factor, and prove upper bounds for mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…By (1.4), these graphs have surplus at most 𝑂(𝜆𝑛) = 𝑂((𝑛𝑑) (𝑟+1)∕(𝑟+2) ), which shows that (1.3) would be optimal for all odd 𝑟. Regarding this problem, Zeng and Hou [24] showed that sp(𝑚, 𝐶 𝑟 ) ⩾ 𝑚 (𝑟+1)∕(𝑟+3)+𝑜 (1) for all odd 𝑟, and very recently, Fox, Himwich and Mani [14] improved the surplus to Ω 𝑟 (𝑚 (𝑟+5)∕(𝑟+7) ). We settle this problem completely by proving the following tight result, which confirms the conjecture of Alon, Krivelevich and Sudakov [5].…”
Section: Cycles Of Odd Lengthmentioning
confidence: 96%
See 2 more Smart Citations
“…By (1.4), these graphs have surplus at most 𝑂(𝜆𝑛) = 𝑂((𝑛𝑑) (𝑟+1)∕(𝑟+2) ), which shows that (1.3) would be optimal for all odd 𝑟. Regarding this problem, Zeng and Hou [24] showed that sp(𝑚, 𝐶 𝑟 ) ⩾ 𝑚 (𝑟+1)∕(𝑟+3)+𝑜 (1) for all odd 𝑟, and very recently, Fox, Himwich and Mani [14] improved the surplus to Ω 𝑟 (𝑚 (𝑟+5)∕(𝑟+7) ). We settle this problem completely by proving the following tight result, which confirms the conjecture of Alon, Krivelevich and Sudakov [5].…”
Section: Cycles Of Odd Lengthmentioning
confidence: 96%
“…The study of MaxCut in H$H$‐free graphs was initiated by Erdős and Lovász (see [12]) in the 70s, and has received significant attention since then (e.g. [2, 3, 5, 6, 14, 21, 22, 24]). For a graph H$H$, define spfalse(m,Hfalse)${\rm sp}(m,H)$ as the minimum surplus spfalse(Gfalse)=mcfalse(Gfalse)m/2${\rm sp}(G)={\rm mc}(G)-m/2$ over all H$H$‐free graphs G$G$ with m$m$ edges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation